Influence of different complexity levels of road traffic models on air quality modelling at street scale - Vicente, Bruno (2019)
Urban mobility accounts for 38 and 19% of nitrogen oxide (NO x ) and particulate matter (PM) emissions at European urban areas, respectively. Despite of all the technological development around automobile industry, urban areas are still facing problems related to exposure to high levels of air pollutants. Increasing the accuracy of both emissions and air quality modelling from road traffic is a key-issue for the management of air pollution in road transport sector. This study assessed the influence of using different road traffic emission models on the accuracy of air quality modelling with street-level resolution, having as a case study an urban area located on the centre region of Portugal. Two emission models, with different complexity levels regarding the ability to characterise the traffic dynamics were analysed, namely, transport emission model for line sources (TREM) and vehicle-specific power (VSP), based on data obtained in an experimental campaign. To perform the air quality simulations, the pollutant dispersion in the atmosphere under variable wind conditions (VADIS) model was used and two pollutants were analysed: NO x and PM10. The results showed that the magnitude of PM10 and NO x concentrations were result of a conjoint influence of traffic dynamics and meteorological conditions. Comparison between measured and modelled data showed that the VADIS model could track the evolution of NO x levels, for both emission models considered, displaying a high correlation (> 0.8) between traffic-related NO x emissions and NO x concentrations. For PM10, VADIS model is more sensitive to the differences in the emissions calculation; however, it was observed that the traffic-related PM10 emissions accounts 1.3–8.4% to the PM10 concentration levels at the study area.